Genetically unresolved case of Rauch-Steindl syndrome diagnosed by its wolf-hirschhorn associated DNA methylation episignature - McConkey, Haley; White-Brown, Alexandre; Kerkhof, Jennifer; Dyment, David; Sadikovic, Bekim (Frontiers in Cell and Developmental Biology, 2022)
Wolf-Hirschhorn syndrome (WHS) is caused by deletion of a critical region of the short arm of chromosome 4. Clinical features of WHS include distinct dysmorphic facial features, growth restriction, developmental delay, intellectual disability, epilepsy, and other malformations. The NSD2 gene localizes within this critical region along with several other genes. Pathogenic variants in NSD2 cause Rauch-Steindl (RAUST) syndrome. Clinical features of RAUST syndrome partially overlap with WHS, however epilepsy and the recognizable facial gestalt are not observed. Here, we report a case of a young boy who presented with developmental delay, dysmorphic features and short stature. After negative chromosomal microarray and whole exome sequencing, genomic DNA methylation episignature analysis was performed. Episignatures are sensitive and specific genome-wide DNA methylation patterns associated with a growing number of rare disorders. The patient was positive for the WHS episignature. Reanalysis of the patient’s exome data identified a previously undetected frameshift variant in NSD2, leading to a diagnosis of RAUST. This report demonstrates the clinical utility of DNA methylation episignature analysis for unresolved patients, and provides insight into the overlapping pathology between WHS and RAUST as demonstrated by the similarities in their genomic DNA methylation profiles.